The Influence of Customer Review, Digital Marketing, and Price on Glad2glow Skincare Purchase Decisions on Shopee - Rika Amelia, Agustin (Proceeding Kilisuci International Conference on Economic & Business, 2025)
Research aim: The purpose of this study is to determine the influence of customer reviews, digital marketing, and price on Glad2glow skincare purchase decisions both partially and simultaneously. Design/Methode/Approach: The approach used in this study is a quantitative approach, a type of descriptive research, a sampling technique used by 40 respondents, and a data analysis technique using multiple linear regression, a classical hypothesis test, a crystallinity coefficient (d2), and validity and reliability testing were analyzed with the SPSS 24 program. Research Finding: The results show that there is a significant influence between customer reviews, digital marketing, and price simultaneously on purchase decisions. Theoretical contribution/Originality: This research paper provides a deeper understanding of the development of purchase decision theory by highlighting the role of consumer reviews and effective digital marketing strategies in building brand awareness and awareness. In addition, this study deepens our understanding of the impact of dynamic pricing and discounts on purchasing behavior, especially when it comes to skincare trends and provides a baaru perspective on online marketing research. Practical / Policy implication: These findings can help businesses manage customer reviews, leverage creative digital marketing, and set competitive prices. By optimizing these three factors, companies can increase competitiveness and customer satisfaction by increasing consumer trust, expanding market reach, and facilitating purchasing decisions. Research limitations: The limitations of this research include focusing on Glad2glow skincare products on shopee, so the results cannot be generalized to other products or platforms. The study also only looked at the impact of customer reviews, digital marketing, and price without considering other factors and focused on the younger generation of consumers.